Discovery of a self-healing catalyst for the hydrolytic dehydrogenation of ammonia borane. Issue 41 (8th April 2019) - Kinik, F. Pelin; Nguyen, Tu N.; Oveisi, Emad; Valizadeh, Bardiya; Ebrahim, Fatmah Mish; Gładysiak, Andrzej; Mensi, Mounir; Stylianou, Kyriakos C.
Abstract : Sustainable catalysts based on earth-abundant elements are considered as economical alternatives to precious-metal-bearing catalysts and could be impactful for many applications. Abstract : Sustainable catalysts based on earth-abundant elements are considered as economical alternatives to precious-metal-bearing catalysts and could be impactful for many applications. Self-healing sustainable catalysts, which in addition to their 'green' characteristic can spontaneously repair themselves without the need of applying heat, pressure or electrochemical bias, are particularly desirable for numerous large-scale chemical processes. Herein, we present the discovery of such a catalyst, named SION-X, for the hydrolytic dehydrogenation of ammonia borane (AB, NH3 BH3 ). SION-X, with the chemical formula of CuII2[(BO)(OH)2 ](OH)3, is the synthetic form of the mineral Jacquesdietrichite and, following in situ reduction, catalyzes the release of almost all 3 equivalents of hydrogen (H2 ) from 1 equivalent of AB. During the reaction, the Cu II ions in SION-X are reduced to Cu 0 nanoparticles, and after the reaction, following exposure to air, they are oxidized re-forming SION-X . As a consequence, the catalytic activity of SION-X toward the production of H2 from AB remains unchanged over many cycles. The self-healing catalysis of SION-X in the absence of any extra energy input gives a new perspective in heterogeneous catalysis for energy-related applications.